Artemisia capillaris with two novel active compounds, Kawarayomogin I and II, inhibits HYBID (KIAA1199) expression as well as hyaluronic acid degradation - Kazal Boron Biswas; Yuka Kawai; Satoshi Nakagawa; Kyoko Kanai; Hiroyuki Kojima; Teruaki Masutani; Masayoshi Oyama; Arunasiri Iddamalgoda; Kotaro Sakamoto (Scientific Reports)
Abstract Hyaluronic acid (HA) is an important component of the skin’s extracellular matrix, and its degradation leads to wrinkles. Hyaluronan-binding protein involved in hyaluronan depolymerization (HYBID) is the main factor responsible for HA degradation in dermis. This study aimed to identify natural plant materials that can effectively suppress HYBID expression and protect HA from degradation. Screening of various plant extracts was performed for the inhibition of histamine-induced mRNA expression of HYBID in normal human dermal fibroblasts (NHDF). The molecular size distribution of HA was evaluated by incubating fluorescein isothiocyanate (FITC)-labeled large HA (1200–1600 kDa) in NHDF for certain time followed by measuring different sizes of FITC-labeled HA in the cultured medium by HPLC. Among 380 plant extracts, we found that Artemisia capillaris flower extract (ACFE) was the most effective agent in both suppressing HYBID expression as well as protecting large HA from degradation. Subsequent mechanism elucidation studies showed that ACFE epigenetically regulates the expression of HYBID by modulating the expression of a specific miRNA, miR-486-5p, which is known to directly target and inhibit HYBID expression. Our active compound search identified 1-caffeoyl-3-hydroxybutane and 3-caffeoyl-1-hydroxybutane in ACFE as new compounds, which we named Kawarayomogin I and Kawarayomogin II, respectively. This is the first report to show that Artemisia capillaris with two novel active compounds inhibits HYBID expression as well as hyaluronic acid degradation, and therefore, could be used as possible agent for cosmeceutical potential.